2022
DOI: 10.1093/jb/mvac052
|View full text |Cite
|
Sign up to set email alerts
|

Novel small synthetic HIV-1 V3 crown variants: CCR5 targeting ligands

Abstract: The CCR5 antagonism represents a promising pharmacological strategy for therapeutic intervention, as it plays a significant role in reducing the severity and progression of a wide range of pathological conditions. Here we designed and generated peptide ligands targeting the chemokine receptor; CCR5 that were derived from the critical interaction sites of the V3 crown domain of envelope protein glycoprotein gp120 (TRKSIHIGPGRAFYTTGEI) of HIV-1 using computational biology approach and the peptide sequence corres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 122 publications
(81 reference statements)
0
1
0
Order By: Relevance
“…CXCR4 and CCR5 are chemokine receptors and members of the G-protein-coupled class family; they have the role of mediating leukocyte development, trafficking, angiogenesis, and immune response [ 126 ]. CXCR4 and CCR4 are attractive candidates for cancer studies since they have been reported to modulate physiological processes associated with proliferation, survival, tumor growth, invasions, and epidermal growth factor receptors [ 127 , 128 ]. CXCR4 has been a consistent marker throughout predominant oncological diseases, including lung cancer [ 129 , 130 ] and PCa [ 131 ].…”
Section: Hiv/aids Malignancies In Cd4+/cxcr4/ccr5-infected Cells Incl...mentioning
confidence: 99%
“…CXCR4 and CCR5 are chemokine receptors and members of the G-protein-coupled class family; they have the role of mediating leukocyte development, trafficking, angiogenesis, and immune response [ 126 ]. CXCR4 and CCR4 are attractive candidates for cancer studies since they have been reported to modulate physiological processes associated with proliferation, survival, tumor growth, invasions, and epidermal growth factor receptors [ 127 , 128 ]. CXCR4 has been a consistent marker throughout predominant oncological diseases, including lung cancer [ 129 , 130 ] and PCa [ 131 ].…”
Section: Hiv/aids Malignancies In Cd4+/cxcr4/ccr5-infected Cells Incl...mentioning
confidence: 99%